(untitled) (Journal of Family Sciences, 2023)
Boys perceive the role of a father based on what he sees, namely the role of their father in the family. This study aimed to identify communication, father-son attachment, and husband’s role based on student perceptions. Sixty male IPB students from villages and cities were respondents in this study. Based on the results of the study, it was found that there was no difference in communication, father-son attachment, and the perception of the husband’s role between students from urban and rural areas. Therefore, the level of communication is in the medium category, attachment is in the safe category, and the perception of the husband’s role is in the medium category. Based on the regression test, it is known that father-son communication has a significant positive effect on the perception of the husband’s role. So, the higher the communication between father and son, the better the perception of the husband’s role in the division of tasks, openness with partners, accountability for the use of resources, and agreement on achieving family goals. The theoretical implication of this research is to prove that father-son communication affects sons’ perceptions of the father’s role; in practice, good father-son communication makes boys open with their partners, take responsibility, and share household chores.